PENGEMBANGAN APLIKASI ARSITEKTUR E-COMMERCE RAFSYA BERBASIS WEBSITE - Yeremia Andrew Sumolang; Intan Oktafiani; Agung Muhammad Rizki; Rido Nur Rahman; Fransiskus Xaverius; Angela Trinata Saragih; Sarah Allya Fawziah (JURNAL TEKNOLOGIA, 2022)
Architects in Indonesia (senior architects and freelance architects) still find it difficult to sell architectural design products. Especially for architects who are outside the island of Java. So we need a website-based e-commerce application specifically for selling architectural product designs for the media for architects and prospective buyers to make buying and selling interactions that are more efficient and effective. This article discusses the development of a website-based Rafsya architecture e-commerce application, starting from the creation of software requirements specifications to the implementation and testing stages. The purpose of this article is to design an application that can make it easier for prospective customers to choose a house design, make it easier for prospective buyers to find architectural product designs, and provide job vacancies as well as architect promotion media. The data collection methods used are interviews, surveys, and literature studies. Meanwhile, the application development method uses the Agile method. The result of this research is a website-based Rafsya e-commerce architecture application which is designed according to the software requirements specification. Keywords: application development, e-commerce architecture, product design architecture.